Production Analysis and Scientific Mapping on Flipped Classroom Research During Covid-19 - Hasan Nuurul Hidaayatullaah; Nadi Suprapto; Titin Sunarti; Tsung-Hui Cheng (Studies in Learning and Teaching, 2022)
This research aimed to analyze the production and scientific mapping of Flipped Classroom (FC) research during Covid-19. The bibliometric method was applied using the Scopus database source, and data were analyzed using the VOSviewer. The results of the study are: (1) The trend of FC publication during Covid-19 continues to increase; (2) English is the primary language used in the FC research; (3) Top publication sources are articles published in journals; (4) The top most prolific writers are Lewin, D, R. and authorship patterns resulted in 22 strongly connected authors; (5) The top countries and institutions in conducting FC research during Covid-19 are the United States and the University of Pennsylvania; (6) The author's most used keywords in the top five are FC, Covid-19, students, e-learning, and teaching; (7) The most citations occurred in articles published in 2020 with a total of 405 citations written by Chick et al. in the field of educational technology studies; and (8) The network and overlay visualization of the FC research consist of four clusters representing four themes regarding the FC during Covid-19. The FC approach can be described as a popular educational model among researchers.